Pharmacokinetics of meloxicam, carprofen, and tolfenamic acid after intramuscular and oral administration in Japanese quails (Coturnix coturnix japonica) - Turk, Erdinc; Tekeli, Ibrahim Ozan; Corum, Orhan; Durna Corum, Duygu; Kirgiz, Fatma Ceren; Cetin, Gul; Arslan Atessahin, Dilek; Uney, Kamil (Wiley, 2021)
AbstractThe aim of this study was to determine the pharmacokinetics of meloxicam (MLX), carprofen (CRP), and tolfenamic acid (TA) in Japanese quails (Coturnix coturnix japonica) following intramuscular (IM) and oral administration at doses of 1, 10, and 2 mg/kg, respectively. A total of 72 quails were randomly divided into 3 equal groups as MLX, CRP, and TA. Each group was separated into two sub‐groups that received IM and oral administration of each drug. Plasma concentrations of MLX, CRP, and TA were determined using HPLC‐UV and analyzed by non‐compartmental method. The t1/2ʎzand MRT of MLX, CRP, and TA after oral administration were similar to those after IM administration. The Vdarea/F of MLX, CRP, and TA after IM administration was 0.28, 2.05, and 0.20 L/kg. The Cl/F of MLX, CRP, and TA after IM administration was 0.12, 0.19, and 0.09 L/h/kg. MLX, CRP, and TA after oral administration showed significantly lower Cmaxand longer Tmaxcompared with IM administration. The relative bioavailability of MLX, CRP, and TA following oral administration in quails was 76.13%, 61.46%, and 57.32%, respectively. The IM and oral route of MLX, CRP, and TA can be used for the treatment of various conditions in quails. However, further research is necessary to determine the pharmacodynamics and safety of MLX, CRP, and TA before use in quails.
Keywords: Carbazoles; Administration, Oral; Animals; ortho-Aminobenzoates; Coturnix; Meloxicam; 3. Good health